The extend and nature of curriculum change in the historically black technical colleges in the Limpopo Province - Bopape, Matome Zacharia (University of Limpopo, 2003)
Refer to document
Thesis (M. Dev.) -- University of Limpopo, 2003
Keywords: Curriculum change; Historically black technical colleges; Limpopo Province; Curriculum change - South Africa - Limpopo; Education - Research